Efektivitas Permainan Ular Tangga sebagai Media Edukasi Kesehatan Gigi bagi Anak Sekolah Dasar - Hendry Boy; Sukarsih Sukarsih; Khoirunisa Aulia Ayuningtyas; Mira Sri Gumilar (Jurnal Sehat Mandiri, 2024)
Lack of dental and oral health knowledge can lead to dental and oral health problems. Dental and oral health problems that are often experienced as caries, periodontitis, gingivitis and tartar. One of the risk populations is elementary school children. Providing dental and oral health education can reduce the risk of dental and oral health problems. One of the educational media that needs to be created to attract children's interest in learning is the snakes and ladders game. This study aims to examine the effectiveness of the snakes and ladders education media on dental and oral health knowledge in class IV students at SDN 131/IV Jambi City. The method used in this research is a Quasi Experimental Design. Based on the calculation of the minimum sample size, it was determined that the subjects participating in this study amounted to 32 samples. Questionnaires are used as a research data collection tool. The data obtained will be analyzed using univariate and bivariate analysis. The research results on maintaining oral health before and after education using snakes and ladders had an average value of 5.06 to 11.13. Knowledge before and after education with the demonstrative method had an average value of 4.94 to 7.63. Statistically, there was a significant difference between treatment and control (P=0.000). Counseling using the snakes and ladders game as a medium for dental and oral health knowledge is effective in enhancing elementary school children's understanding of dental and oral health.